2000
DOI: 10.1007/s002340000326
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal low-signal brain lesions on T2 * -weighted gradient-echo imaging

Abstract: Multifocal small low-signal lesions on T2*-weighted gradient-echo (GE) MRI are reported to be common in the brain of hypertensive patients. We examined factors associated with these lesions. For one year, we routinely obtained T2*-weighted GE images (TR 1000 TE 30 ms, flip angle = 20 degrees) in all adult patients (314) who underwent brain MRI in our hospital, using a 1.5 T superconducting magnet. Patients with multifocal small low-signal lesions with a known or presumed pathogenesis or any condition which may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 0 publications
0
25
0
1
Order By: Relevance
“…5,[13][14][15][16][17] In their study of patients with a history of atherosclerosis, Kwa et al 5 found that hemosiderin deposits visualized with MRI were significantly associated with cerebral white matter lesions.…”
Section: Discussionmentioning
confidence: 99%
“…5,[13][14][15][16][17] In their study of patients with a history of atherosclerosis, Kwa et al 5 found that hemosiderin deposits visualized with MRI were significantly associated with cerebral white matter lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Existe un incremento en la incidencia de MH dependiendo del grupo de pacientes seleccionado. Así, se reporta una incidencia en individuos neurológicamente asintomáticos de un 6,4%, la mayoría hipertensos, mayores de 65 años, con MH ubicadas principalmente en ganglios basales y tálamo, asociadas a lesiones isquémicas lacunares antiguas y leucoariosis (27) ; un 10% en pacientes con infarto al miocardio (28) ; un 21% a 47% en pacientes con (ECV) isquémico no seleccionado (26,29) ; un 46% a 62% en pacientes con infarto lacunar agudo, que aumenta a un 68% cuando son múltiples (29,31) y un 50% a 80% en pacientes con HE primaria (32)(33)(34)(35)(36) . Recientemente se ha descrito la presencia de MH en la angiopatía cerebral B-amiloidea, ubicadas en la región córtico-subcortical, que se asocian fuertemente a HE e incluso pueden precederla (37)(38)(39)(40) .…”
Section: Discussionunclassified
“…HD patients have many risk factors for hemorrhagic stroke, such as hypertension, systemic heparinization, ultrafiltration to treat fluid accumulation, poor platelet adhesion, and infection. 23) Previous studies have shown a positive correlation between microbleeds and hypertension, 25,26,28) but the possible causative factor for microbleeds in HD patients has not been identified. In our study, the incidence of hypertension was significantly higher in the HD patients than in the controls.…”
Section: Discussionmentioning
confidence: 99%
“…12,[14][15][16]20,21,28) T 2 *-weighted gradient-echo magnetic resonance (MR) imaging detected microbleeds in more than 50% of patients with intracerebral hemorrhage. 25,27) The number of microbleeds may be correlated with intracerebral hemorrhage.…”
Section: Introductionmentioning
confidence: 99%